Bipedal humanoid robot - Zayer, Iman Ahmed; Aris, Ishak; Marhaban, Mohammad Hamiruce; Ishak, Asnor Juraiza (Universiti Putra Malaysia Press, 2018)
The new millennium witnessed increasing attention to the field of robotics, especially the development of humanoid bipedal robot. Attention is noticed from the increasing number of publications as a result of a multitude of humanoid projects for commercial and academic goals. This paper briefly visits the recent activities in this field, highlighting the importance and motivation behind adopting bipedal humanoid projects, particularly underlining biologically inspired design concept, bipedal locomotion and communication. Ultimately, emphasising on power-efficient design. The problem of endurance and effective duty cycle were presented. Finally, potential future application for the humanoid robot was briefly listed.